Plant species diversity among ecological species groups in the Caspian Sea coastal sand dune; Case study: Guilan Province, North of Iran - MOKARRAM RAVANBAKHSH; TAYYEBEH AMINI; SAYED MOHSEN NASSAJ HOSSEINI (Society for Indonesian Biodiversity, 2015)
Ravanbakhsh M, Amini T, Hosseini SMN. 2015. Plant species diversity among ecological species groups in the Caspian Sea coastal sand dune; Case study: Guilan Province, North of Iran. Biodiversitas 16: 16-21. Biodiversity is often discussed in terms of species diversity is concentrated. Species diversity is one of the important characteristics of biological communities and its as a functionof the number and size represent populations of species in a special geographic region.The aim of this study was to identification ofecological species groups and investigates the diversity among ecological species groups. The research area comprises a coastal dunesystem in northern of Guilan Province, Iran. Vegetation sampling was carried out along 22 shore perpendicular transects, approximately500-m long. A total of 62 plot of 25 square meters were taken in transects. In each sampled plot, the cover percentage value of eachspecies was estimated using Bran-Blanquet scales. Vegetation classified using Two-Way Indicator Species Analysis (TWINSPAN). Thecomparison of diversity indices among groups were performed with ANOVA test. The results revealed that there were 232 plant taxaand 8 ecological species group in the region. Results of analysis of variance in species diversity indices showed significant differencesamong the groups in terms of biodiversity indices. The survey of variation in the groups showed that groups 5 and 6 had the highest andgroups 1, 2, 3, and 7 had the lowest indices. Checking of the group's position with high diversity in comparison with other groups in thiscoastal area indicates that the group settled on the coastal land with stabilized soil and proper distance from the sea had higher diversityindices.